Síndrome de Miller-Fisher seguido por vacuna Sputnik V - Ángel Chacón-Pazmiño (Asociación Colombiana de Infectología, 2022)
Miller-Fisher syndrome (MFS), defined as a rare variant of Guillain-Barré syndrome (GBS), is characterized by the classic triad of ataxia, areflexia, and ophthal-moplegia. It is a demyelinating polyneuropathy resulting from a deregulated autoimmune response secondary to infection by viruses and bacteria. SMF and GBS have been described during the COVID-19 pandemic. There are some reports in the literature of GBS after vaccination for COVID-19. In contrast, reports of post-vaccination FMS for SARS-CoV-2 are scarce in the literature. A 75-year-old patient is presented who consults for asthenia, adynamia, and difficulty swallowing that progresses to respiratory distress. She refers to the application of the Sputnik V vaccine as an important antecedent. During the hospital stay, the diagnosis was made by electromyography and nerve conduction study of GBS variant SMF. The objective is to expose a post-vaccination SMF to SARS-CoV-2 with the biological Sputnik V and highlight the importance of this background for surveillance in clinical practice and future research.